Directed Evolution of a Fluorinase for Improved Fluorination Efficiency with a Non‐native Substrate. Issue 46 (14th October 2016) - Sun, Huihua; Yeo, Wan Lin; Lim, Yee Hwee; Chew, Xinying; Smith, Derek John; Xue, Bo; Chan, Kok Ping; Robinson, Robert C.; Robins, Edward G.; Zhao, Huimin; Ang, Ee Lui
Abstract: Fluorinases offer an environmentally friendly alternative for selective fluorination under mild conditions. However, their diversity is limited in nature and they have yet to be engineered through directed evolution. Herein, we report the directed evolution of the fluorinase FlA1 for improved conversion of the non‐native substrate 5′‐chloro‐5′‐deoxyadenosine (5′‐ClDA) into 5′‐fluoro‐5′‐deoxyadenosine (5′‐FDA). The evolved variants, fah2081 (A279Y) and fah2114 (F213Y, A279L), were successfully applied in the radiosynthesis of 5′‐[ 18 F]FDA, with overall radiochemical conversion (RCC) more than 3‐fold higher than wild‐type FlA1. Kinetic studies of the two‐step reaction revealed that the variants show a significantly improved k cat value in the conversion of 5′‐ClDA into S ‐adenosyl‐l ‐methionine (SAM) but a reduced k cat value in the conversion of SAM into 5′‐FDA. Abstract : Faster Fluorination : Fluorinases are challenging to engineer owing to high substrate specificity. A fluorinase (structure shown) was engineered through directed evolution and the evolved variants showed improved activity with the non‐native substrate 5′‐chloro‐5′‐deoxyadenosine. Kinetics studies revealed a faster first step of the reaction. Structural data suggest that the mutations lead to tighter binding of S ‐adenosyl‐l ‐methionine.